Penerapan Kurikulum Merdeka Belajar dalam Pembelajaran Akidah Akhlak di MTs Ma’arif NU 1 Sokaraja Banyumas - Mangisyatul Azqiya, Dhiyaa; Yahya, MS (Jurnal Pendidikan Agama Islam, 2025)
The Merdeka Curriculum is an educational reform in Indonesia that grants teachers and learners greater autonomy to design learning aligned with students’ interests, developmental stages, and school context. This study describes how the Merdeka Belajar Curriculum is implemented in Aqidah Akhlaq instruction at MTs Ma’arif NU 1 Sokaraja and analyzes supporting and inhibiting factors. A descriptive qualitative approach was employed. Data were gathered through classroom observations, in-depth interviews (teachers, school leadership, curriculum vipe principal), and document review of lesson plans and teaching modules. Data analysis followed the steps of reduction, display, and conclusion drawing, supported by source and method triangulation. Results indicate that instructional planning incorporates teaching modules, learning goal sequences, and character integration; however, classroom practice remains largely lecture-centered and media use is limited. Supporting factors include leadership support and conducive environmet. Challenges arise from ongoing curriculum adjustment, limited technology-based media, and inadequate facilities and infrastructure. These findings inform efforts to optimize Merdeka Belajar Curriculum practice in faith-based schools